Looking for Experiences in the Inland Areas: Walking in the Bolognese Apennines - Manella, Gabriele (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2024)
The contribution starts from point 2 of the I.Ta.Cà.’s manifesto about the Tourist as a (con) temporary citizen, and it focus on the growth of “experiential tourism”: in other words, the search for a unique and authentic experience in the holiday, the basic importance of human relations and the possibility of multisensory experiences (involving sight, hearing, touch, smell and taste), as well the direct and participant knowledge of local identity. This new scenario calls into question many regions that can enter the tourism market by making use of the infinite possibilities offered by the network and the media, even more important in this pandemic period and for the Italian marginal areas (Aree Interne). This contribution explores the walking sector in the Bolognese Apennines using, in addition to a bibliographic and website search, ten interviews with walkers, guides, members of local institutions and experts in this sector. An important progress has emerged in recent years thanks also to the role of I.Ta.Cà., both in walkers’ flows and in the development of public-private networks to manage them, but also critical issues in monitoring the phenomenon and in strengthening interactions between tourists and local actors during and after the trip.